A Q‐method survey of stream restoration practitioners in the Driftless Area, USA. (8th April 2022) - Lundberg, Emma; Gottschalk Druschke, Caroline; Booth, Eric G.
Abstract: Stream restoration has become increasingly common, both globally and specifically in the United States. Though stream restoration has become a common freshwater management practice, there are debates around what constitutes "success" in restored systems and whether this success should incorporate both scientific and stakeholder‐defined endpoints. In our study context, the Upper Mississippi River Basin's Driftless Area, conflicts over stream restoration practices often center on the management and use of Driftless Area streams, as practitioners navigate competing perspectives about restoration approaches alongside tensions over whose needs and interests should be prioritized in restoration planning and implementation. Based on the importance of stream restoration practitioner perspectives for mediating uncertainty and shaping on‐the‐ground projects, we asked (a) What are the main areas of conflict that emerge around Driftless Area stream restoration? (b) Can stream restoration practitioners be categorized into distinct groups based on their varying perspectives on stream restoration practices in the Driftless Area? (c) If so, what are these groups and how do they map onto the main areas of stream restoration conflict in the Driftless Area? We used Q‐method to identify and describe four perspectives about stream restoration practices and priorities in the Driftless Area. Our results suggest that (a) the differences between groups are related to concerns about best practices for stabilizing streambanks and post‐restoration monitoring. We found that (b) all four Q‐method identified groups agree that floodplain‐stream channel reconnection is an important aspect of restoration projects and that erosion is a big concern in the Driftless Area.